Caracterização e potencial tecnológico de Myrcianthes pungens (guabiju) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
The development of products enriched with natural compounds has been widely investigated in several studies, due to greater consumer demand. Different plant species can provide compounds of interest to different industrial segments. The Myrcianthes pungens (guabij ̇) is considered a source of bioactive compounds, to which antioxidant and antimicrobial properties are attributed. Thus, as guabij ̇ has proven to be a promising raw material, the objective of the research was to evaluate the technological potential of the extracts and essential oils extracted from the leaves and fruits of the guabij ̇ tree. The study was conducted in 5 stages (chapters), initially demonstrating data from the literature on compounds already identified in guabij ̇, in addition to information on chemical constituents in essential oil of species of the Myrtaceae family and techniques for separating compounds. In chapter 2, the following were evaluated the physical and chemical characteristics of the fruits, leaves and seeds. It was observed that the fruits evaluated contained low acidity and high sugar content, such as fructose (7.14 g 100 g-1). The seeds demonstrated a greater predominance of succinic acid (87.01 mg 100 g-1) and a greater sum of the minerals calcium, potassium and sodium. The leaves showed higher ash and protein content (5.57 and 4.82 g 100 g-1) in addition to the highest concentration of carotenoids (562.15 μg g-1). In chapter 3, the extraction of bioactive compounds from guabij ̇ leaves and fruits was optimized, using an experimental design combined with the response surface methodology (RSM). Different combinations of solvent concentration (acetone and ethanol), solute:solvent ratio and temperature were analyzed. The RSM suggested that the best conditions for obtaining bioactive compounds from fruit extracts, in the case of using ethanol, would be a concentration of 50.6%, solute:solvent ratio of 1:30 and a temperature of 50 oC, while for extracts prepared with acetone, a concentration of 46%, solute:solvent ratio of 1:10 and temperature of 50 oC. The optimization of extraction to maximize the bioactive content of leaf extracts indicated the combination of the factors solvent concentration 30%, solute-solvent ratio 1:30 and temperature of 25 °C for use with the solvent ethanol. For the use of acetone, the application of the conditions solvent concentration 70%, solute-solvent ratio 1:30 and temperature of 40 °C resulted in the best condition. Using the optimized parameters, it was observed that the combination with ethanol extracted a higher content of phenolic compounds in the guabij ̇ fruits (2666.27 mg kg-1) and the solution with acetone obtained a higher content for the leaves (6555.32 mg kg-1). Both extracts demonstrated antimicrobial capacity against pathogenic microorganisms. In chapter 4, the optimized extracts that indicated the highest concentration of bioactive compounds were applied in the preparation of yogurts. The incorporation of leaf and fruit extracts in different proportions (5 and 10%) favored an increase in the concentration of phenolic compounds, flavonoids and anthocyanins, as well as antioxidant activity in all enriched formulations, although with a more expressive result in the sample with leaf extract (FO10). However, the viability of lactic acid bacteria was maintained during 21 days of storage, in the range of 106 and 109 CFU g-1 . In the last stage, the guabij ̇ leaves and fruits were used to extract the essential oil (EO), which revealed the predominance of chemical compounds from the hydrocarbon sesquiterpene class (57.89%), which together with other identified constituents demonstrated an aroma considered fruity-herbaceous-woody. The obtained EOs showed antioxidant and antimicrobial potential, with MIC values being more expressive in the EOs from the leaves, especially against E. coli and Salmonella (80.92 and 80.16 μg mL-1). The findings of this research contribute to the appreciation of guabij ̇ as a source of natural compounds, with potential for application in food products, such as yogurt.
Keywords: Compostos bioativos; Capacidade Antioxidante; Atividade Antimicrobiana; Iogurte; Compostos químicos; Ciências Agrárias